Decreased Salivary Cortisol in Recurrent Aphthous Stomatitis Treat-ed with Topical Steroids - Hendri Susanto; Puout Kendarwati; Kholifastia Imanusti; Laxmi Widyanigsih; Sri Budiarti; A Supriatno (Islamic Dental Association of Iran, 2019)
Background and Aim: Stress has been associated with recurrent aphthous stomatitis (RAS). The common treatment of RAS is a topical steroid. This study aimed to investigate the difference of salivary cortisol between RAS patients treated with a topi-cal steroid and those without treatment. Materials and Methods: Thirty-two female patients with RAS participated in this case-control study and were randomly divided into two groups: the case group (n=16) treated with a topical steroid and the control group (n=16) without any treatment. The inclusion criteria comprised of non-pregnant women with RAS. The exclusion criteria consisted of having other diseases, taking medications, and smoking. All subjects were examined for pre- and post-treatment salivary cortisol at the onset of the ulcers in the case group and when the ulcers were healed in the control group. Data on the characteristics of the subjects were collected and presented descriptively, and the difference in salivary cortisol was analyzed using Mann-Whitney-U test and independ-ent t-test with a 95% confidence interval (CI) in SPSS 17.00 software. Results: The mean salivary cortisol in the pre-treatment group (10.51±5.15 ng/ml) was higher than that in the post-treatment group (9.30±3.77 ng/ml). The mean salivary cortisol at the onset of RAS (9.55±4.03 ng/ml) was lower than when RAS was healed (13.07±3.82 ng/ml) in the control group. There was a significant difference in the mean of pre- and post-treatment salivary cortisol levels between the case and the control groups (P<0.05). Conclusion: Topical steroids may not only reduce inflammation of oral ulcers but also may reduce salivary cortisol in RAS.